Efficacy and safety of different drugs for the treatment of bacterial vaginosis: a systematic review and network meta-analysis - Gu, Yanhong; Xian, Yi; Li, Qinya; He, Youli; Chen, Kaiyang; Yu, Hui; Deng, Huan; Xiong, Li; Cui, Zhiwei; Yang, Yang; Xiang, Yin (Frontiers in Cellular and Infection Microbiology, 2024)
ObjectiveBacterial vaginosis is a disease caused by vaginal microecology disorder, which seriously affects female health. At present, there are many drugs to treat BV, and this study aims to compare the efficacy and safety of multiple drugs for BV through a network meta-analysis (NMA).MethodsAll studies were sourced from PubMed and Embase databases from the establishment date to April 13, 2023. We evaluated the clinical cure success rate and adverse effects (abnormal increase in vaginal discharge, external genital irritation, and vulvar itching) and performed subgroup analyses of the clinical cure success rate for different modes of administration. All statistical analyses were performed using R and STATA 14.0 software for network meta-analysis.ResultsWe included 42 studies that met the criteria, involving a total of 8382 patients. Network meta-analysis results showed that metronidazole and secnidazole had a higher rate of adverse reactions than placebo (RR 7.06; 95%-CI 2.61-19.10, RR 4.03; 95%-CI 1.63-9.98), the adverse reaction rate of probiotics group was lower than that of metronidazole group (RR 0.44; 95%-CI 0.21-0.93). The clinical cure rate of oral ornidazole was better than clindamycin (RR 16.08; 95%-CI 1.72-150.47), Secnidazole (RR 8.17; 95%-CI 1.66-40.25) and probiotics. Direct meta-analysis results showed that ornidazole had a better clinical cure rate than Secnidazole (RR 1.22; 95%-CI 1.10-1.34), oral ornidazole had a better clinical cure rate than Secnidazole (RR 1.23; 95%-CI 1.11-1.36). The clinical cure rate of vaginal application of sucrose was better than metronidazole (RR 1.12; 95%-CI 1.03-1.21) and metronidazole had a lower clinical cure rate than probiotics (RR 0.68; 95%-CI 0.52-0.88).ConclusionsThe results of this systematic review and network meta-analysis suggest that ornidazole may be an effective alternative for the treatment of BV, and that sucrose and probiotics are potential BV treatments that need to be validated by more high-quality clinical studies in the future.